Beaivváš nieida mánáidgirjji dulkon: Govviduvvon kulturdovddaheamit ja árvvut Marry Áilonieida Somby girjjis Beaivváš nieida - Logje, Mikkel Nils (UiT Norges arktiske universitet, 2022)
The thesis examines the children's book Beaivváš nieida by Marry Áilonieida Somby. It is based on an old myth about how the Sun's daughter taught the Sámi people to tame reindeer. An overview of the cultural background is given: myths, stories and yoiks in Sámi society, and Sámi child rearing. The book is analysed using narratological theories - in particular Genette's chronology, Barthes' intertext categories, Gadamer's reception theory, Propp's functions, and Greimas' actant model - to see how the story about the Sun's daughter, and Sámi stories in general, differs from the stories these writers did their research on. Finally, the book is analysed in relation to Sámi society and history: the Norwegianisation period, the pre-Christian pagan faith of the Sámi, the natural lifestyle and attitude towards nature of the Sámi people, the cultural significance of marking reindeer, the role of yoiks and stories in Sámi child rearing, and the importance of writing children's books in the Sámi language. Dát bargu dutká Marry Áilonieida Sombby mánáidgirjji Beaivváš nieida. Dat vuolgá dološ sámi máidnasis Beaivváš nieidda birra ja movt son oahpahii sápmelaččaid dápmat gottiid. Girjji kultuvrralaš duogáš lea: myhtat, muitalusat ja luođit sámi servvodagas, ja sámi mánáidbajásgeassin. Girji dulkojuvvo narratologiija teoriijain - earenoamážit Genette kronologiija, Barthes:a interteaksta kategoriijat, Gadamer:a resepšunteoriija, Propp:a funkšuvnnaid, ja Greimas:a aktántamodealla - dutket movt Beaivváš nieidda muitalus, ja sámi muitalusat obbalaččat, earránit dain muitalusain maid čállit dutke go huksejedje teoriijaáset. Loahpas, girji dulko sámi servvodaga ja historjá ektui: dáruiduhttima, ovdaristtalaš oskku sápmelaččain, sámi eallinvuogi ja luondduoainnu, kultuvrralaš mearkkašumi bohccomearkumis, movt luođit ja muitalusat adnojit sámi mánáidbajásgeassimis, ja árvvu čállit sámegillii mánáidgirjjiid. Keywords: Marry Áilunieida Somby, the Sun's Daughter, Beaivváš nieida, Sámi children's literature, Sámi myths, narratology